Pengaruh Penerapan Big Data Analisis Dalam Pendeteksian Fraud : Literature Review - Leni Gaswira; Tuti Meutia (Jurnal Riset Akuntansi, 2024)
In the context of increasingly complex business environments and globalization, fraud detection has become highly critical to mitigate its negative impacts on organizations. One effective innovation in this regard is the utilization of big data analysis. Big data refers to large and complex datasets obtained from various organizational activities. The purpose of this research is to determine the influence of using big data analysis in fraud detection. The research method employed is a literature review, which indicates that big data analysis plays a significant role in enhancing auditors' capabilities in detecting fraud. By providing auditors access to a wide range of data sources, improving the efficiency of analytical processes, and enabling the identification of suspicious patterns, big data analysis assists in uncovering fraud more efficiently. The results show that big data analysis has a positive influence on enhancing fraud detection capabilities.